Yak introgression into Tibetan Yellow cattle: evidences from mitochondrial DNA D-loop sequence analysis and β-lactoglobulin genetic variants - Liu, Zhengxin; Lu, Bangmin; Mao, Yongjiang; Li, Yuping; Jin, Suyu; Zheng, Yucai (The Indian Journal of Animal Sciences, 2012)
The objective of this study was to investigate the possible introgression of highland yak (Bos grunniens) into Tibetan Yellow cattle (Bos taurus) based on milk protein and mtDNA D-loop analysis. Tibetan Yellow cattle (43) were used to assay polymorphisms of β-lactoglobulin (β-Lg) and to extract genomic DNA for the PCR amplification of mtDNA D- loop. Native polyacrylamide gel electrophoresis (PAGE) of milk β-Lg showed that 3 milk samples exhibited the yak- specific β-Lg E variant among the 43 milk samples tested. mtDNA D-loop sequences were successfully amplified by PCR using genomic DNA extracted from milk. A total of 16 sequences of the mtDNA D-loop were obtained for analysis, which contained 133 variable sites (97 parsimony-informative sites and 36 single sites) and defined 15 different haplotypes. The 3 Tibetan Yellow cattle carrying β-Lg E variant were exactly clustered with yak when mtDNA D-loop sequences were employed for cluster analysis, while other yaks assayed (13) clustered with cattle. This research demonstrated that there existed matrilineal introgression of yak during the evolution or natural breeding of Tibetan Yellow cattle population on Qinghai-Tibet plateau.